Chest CT accuracy in the diagnosis of SARS-CoV-2 infection: initial experience in a cancer center - Barbosa, Paula Nicole Vieira Pinto (2020)
Objective: To evaluate the accuracy of chest computed tomography (CT) in patients with suspected severe acute respiratory syndrome-related coronavirus-2 (SARS-CoV-2) infection at a cancer center. Materials and Methods: This retrospective single-center study selected 91 patients who had chest CT and real-time polymerase chain reaction (RT-PCR) test collected at the same day. CT results were classified in negative, typical, indeterminate or atypical findings. Diagnostic accuracy, sensitivity and specificity were calculated for two different scenarios: in the first, only typical findings on CT were considered positive; in the second, both typical and indeterminate findings were considered positive. Results: Mean patients’ age was 58.2 years, most were male (60.4%) and had prior diagnosis of cancer (85.7%). CT showed typical findings in 28.6%, indeterminate findings in 24.2% and atypical findings in 26.4%. RT-PCR results were positive for SARS-CoV-2 in 27.5%. The sensitivity, specificity and accuracy in the first and second scenarios were respectively 64.0%, 84.8% and 79.1%, and 92.0%, 62.1% and 70.3%. Conclusion: CT has a high accuracy for the diagnosis of SARS-CoV-2 infection. Different interpretation criteria can provide either high sensitivity or high specificity. CT should be integrated as a triage test in resource-constrained environments during the pandemic to assist in the optimization of PCR-tests, isolation beds and intensive care units.